Billionaire wilderness the ultra-wealthy and the remaking of the American West - Farrell, Justin, 1983- (Princeton studies in cultural sociology., 2020)
"Billionaire Wilderness offers an unprecedented look inside the world of the ultra-wealthy and their relationship to the natural world, showing how the ultra-rich use nature to resolve key predicaments in their lives. Justin Farrell immerses himself in Teton County, Wyoming-both the richest county in the United States and the county with the nation's highest level of income inequality-to investigate interconnected questions about money, nature, and community in the twenty-first century. Farrell draws on three years of in-depth interviews with "ordinary" millionaires and the world's wealthiest billionaires, four years of in-person observation in the community, and original quantitative data to provide comprehensive and unique analytical insight on the ultra-wealthy. He also interviewed low-income workers who could speak to their experiences as employees for and members of the community with these wealthy people. He finds that the wealthy leverage nature to climb even higher on the socioeconomic ladder, and they use their engagement with nature and rural people as a way of creating more virtuous and deserving versions of themselves. Billionaire Wilderness demonstrates that our contemporary understanding of the relationship between the ultra-wealthy and the environment is empirically shallow, and our reliance on reports of national economic trends distances us from the real experiences of these people and their local communities"--